A case report of an 80 year old man with mesenteric panniculitis, a raised lactate and hyperglycaemia. (2015) - Chechi, Moaize; Alsallami, Zeyad; Armstrong, Luke
Highlights: 80 year old presenting with abdominal pain, raised lactate, hyperglycaemia. Radiological diagnosis of mesenteric panniculitis from CT. No clear cause for raised lactate. Patient simultaneously found to be type 2 diabetic—further research warranted. Abstract: Introduction: Mesenteric panniculitis is a rare condition which presents as abdominal pain. It involves benign inflammatory or fibrotic changes affecting the mesentery of the bowel. Presentation of case: An 80 year old man presented with severe abdominal pain of acute onset. He was found to have a high lactate and high blood glucose. He was not a known diabetic. A computed tomography (CT) scan revealed a diagnosis of mesenteric panniculitis, and the patient rapidly responded to steroid treatment. Discussion: Mesenteric panniculitis has been known to present as an acute abdomen. However, an associated high lactate and hyperglycaemia is hitherto unreported in the literature. With no obvious precipitant for an increased lactate, we propose it is potentially caused by the subsequent fat necrosis and regional ischaemia associated with mesenteric panniculitis. Conclusion: This case report underlines the importance of further research into the relationship between mesenteric panniculitis, a high lactate, and diabetes. In addition, short term steroid treatment (one month) seemed to confer the same benefit as long term steroid treatment.